Elaboración y aplicación de módulos electrónicos de potencia con su respectivo manual de prácticas para el laboratorio de ingeniería eléctrica, para la enseñanza de los alumnos de la unidad académica de ciencias de la ingeniería y aplicadas de la Universidad Técnica de Cotopaxi - Semanate Alvarez, Doris Maribel (2015)
The project has as aim to develop and implement power Electronic Modules in the laboratory of Electrical Engineering of the Technical University of Cotopaxi, the same which will help to the academic training of students of the technical careers of the institution. Electronic Power Modules are divided into three themes are: Practice Transistors, practice of SCR and practice of diodes so as to enable students to do internships and complement the knowledge acquired in the classroom, so that in this way both teachers and students can visualize in real time the forms and magnitudes of electrical waves. The rising tide of the power electronic has allowed that these devices to be used in industrial, commercial and residential processes, being this an important matter in the technical courses that the university offers.